Systematic review: unmet supportive care needs in people diagnosed with chronic liver disease - Valery, Patricia C (BMJ Open, 2015)
OBJECTIVE: People with chronic liver disease, particularly those with decompensated cirrhosis, experience several potentially debilitating complications that can have a significant impact on activities of daily living and quality of life. These impairments combined with the associated complex treatment mean that they are faced with specific and high levels of supportive care needs. We aimed to review reported perspectives, experiences and concerns of people with chronic liver disease worldwide. This information is necessary to guide development of policies around supportive needs screening tools and to enable prioritisation of support services for these patients. DESIGN: Systematic searches of PubMed, MEDLINE, CINAHL and PsycINFO from the earliest records until 19 September 2014. Data were extracted using standardised forms. A qualitative, descriptive approach was utilised to analyse and synthesise data. RESULTS: The initial search yielded 2598 reports: 26 studies reporting supportive care needs among patients with chronic liver disease were included, but few of them were patient-reported needs, none used a validated liver disease-specific supportive care need assessment instrument, and only three included patients with cirrhosis. Five key domains of supportive care needs were identified: informational or educational (eg, educational material, educational sessions), practical (eg, daily living), physical (eg, controlling pruritus and fatigue), patient care and support (eg, support groups), and psychological (eg, anxiety, sadness). CONCLUSIONS: While several key domains of supportive care needs were identified, most studies included hepatitis patients. There is a paucity of literature describing the supportive care needs of the chronic liver disease population likely to have the most needs—namely those with cirrhosis. Assessing the supportive care needs of people with chronic liver disease have potential utility in clinical practice for facilitating timely referrals to support services.